Pengaruh Model Pembelajaran Berbasis Masalah terhadap Kemampuan Berpikir Kreatif Matematis - Maria Luthfiana; Lucy Asri Purwasi (Jurnal Pendidikan Matematika:Judika Education, 2018)
The purpose of this study was to determine the effect of problem-based learning models on the ability to think mathematically creative in class VIII of SMP Negeri 6 Lubuklinggau. This study uses a True Experimental Design approach. In this study the sample used were two classes, namely the control class and the experimental class. The average score of mathematical creative thinking abilities that have been obtained by students on the final test in the experimental class is 19.5517 and in the control class an average score of 14.44783 is obtained. Both classes are normally distributed and homogeneous both on the initial and final tests. The collected data were analyzed using t-test. Based on the results of the t-test analysis obtained tcount = 2.5400 and ttable (at a significant level = 0.05) = 2.001. This shows tcount> ttable, so it can be concluded that there is a significant effect of problem-based learning models on the ability of mathematical creative thinking ability of eighth grade students of SMP Negeri 6 Lubuklinggau. Keywords: Mathematical Creative, Problem Based Learning Model